Mechatronic application for agriculture mechanization analysis and education - Mohd Hudzari, Haji Razali; Noordin Asimi, Mohd Noor; Nor Idayu, Othman; Hamim Izuan, Hamdan (2012)
Transport could be considered an essential factor in improving agricultural productivity. An improved transportation helps to reduce spoilage and wastage, empower the farmers as well as having a positive impact on their productivity, income and employment. In this study, the main component in the kit is a brick-shaped computer control programming called the NXT brick. It can take input from one to four sensors and could be controlled by up to three motors, via RJ12 cables, very similar to but incompatible with RJ11 phone cords. The experiment was then successfully conducted. The tyre chosen should not be too narrow or too wide. The effect of a machine on the soil depends on the load on the wheel and the ground pressure it exerted. It is important to note that a high load carrying capacity can be achieved by using a larger tyre and/or a tyre that is inflated at high pressures. For machine weight factor, three weights of load had been loaded into the NXT robot tractor and the result obtained was analysed. The result proved that appropriate tyre size selection is important in reducing soil compaction. In overall, the NXT robot tractor acts as a two wheel drive tractor since the there is insufficient servo motor port to connect with to make it acts as a four wheel drive tractor